Quantitative Evaluation of Acetaminophen in Oral Solutions by Dispersive Raman Spectroscopy for Quality Control. Issue 4 (13th June 2012) - Borio Borio, Viviane G. Viviane G.; Vinha Vinha, Rubens Rubens; Nicolau Nicolau, Renata A. Renata A.; de Oliveira de Oliveira, Hueder Paulo M. Hueder Paulo M.; de Lima de Lima, Carlos J. Carlos J.; Silveira Silveira, Landulfo Landulfo
Abstract : This work used dispersive Raman spectroscopy to evaluate acetaminophen in commercially available formulations as an analytical methodology for quality control in the pharmaceutical industry. Raman spectra were collected using a near-infrared dispersive Raman spectrometer (830 nm, 50 mW, 20 s exposure time) coupled to a fiber optic probe. Solutions of acetaminophen diluted in excipient (70 to 120% of the commercial concentration of 200 mg/mL) were used to develop a calibration model based on partial least squares (PLSs) applied to Raman spectra of solutions and, subsequently, obtain linearity, accuracy, precision (repeatability), and sensitivity of the method using the near-infrared spectroscopy (NIRS) as a gold standard method. This model was used to predict the acetaminophen concentration in commercial samples from different lots of acetaminophen formulations (200 mg/mL) with a PLS-prediction error of about 0.6%. Commercial medicines had PLS predicted concentrations errors below 2.5%, whereas NIRS had an error of about 3.7% compared to the label concentration. It has been demonstrated the applicability of Raman spectroscopy with fiber probe for quality control in pharmaceutical industry of commercial formulations.